APPLYING MACHINE LEARNING TO ANALYZE TUBERCULOSIS SERVICE STANDARDS IN INDONESIA - Yuantari, Maria Goretti Catur; Manglapy, Yusthin M.; Nurmandhani, Ririn; Kusuma, Edi Jaya; Haikal, Haikal; Miarso , Dani (Malaysian Journal of Public Health Medicine, 2026)
Tuberculosis (TB) remains a significant public health challenge in Indonesia, with persistent disparities in service quality. Early identification of substandard TB services is critical to prevent transmission and accelerate elimination efforts. This study developed a machine-learning–based model to classify TB service compliance, identify key predictors, and provide evidence to guide targeted TB control policies. A retrospective design was applied using primary and secondary data from 1,722 TB patients in Semarang City, Indonesia. Three algorithms—Random Forest, K-Nearest Neighbors (KNN), and Boosting—were implemented with 5-fold stratified cross-validation, feature selection via Recursive Feature Elimination (RFE), hyperparameter tuning, and variable importance analysis. Model performance was evaluated based on accuracy, AUC, recall, and F1-score, with particular emphasis on the ability to detect the minority class ("non-compliant services"). The Random Forest model achieved the highest test accuracy (97.7%) with an average AUC of 0.655. However, the high accuracy should be interpreted cautiously, given the highly imbalanced class distribution (96.1% compliant vs 3.9% non-compliant), which limits the model’s ability to detect minority cases. The analysis, therefore, emphasized recall and F1-score for the minority class as indicators of the model’s practical usefulness for early detection. Five key predictors were identified, with anti-TB drug regimen and age contributing most to model performance. The model shows potential as an early warning tool for substandard TB services and can support risk-based interventions. Integration into national health information systems may strengthen decision-making and accelerate TB elimination.